One-Stage Revision with Cage Replacement as Treatment for Refractory Infections after Tibial Tuberosity Advancement in 7 Dogs - Onis, David; Wagter, Henrik; Serck, Boris; Wouters, Erik G.H. (VCOT Open, 2023)
The aim of this article was to report surgical and medical management, and to evaluate complications and outcome of dogs treated for refractory infection after tibial tuberosity advancement (TTA) with a one-stage revision surgery consisting of implant removal and replacement of a TTA cage. It was a retrospective case series. Seven cases were included in this study. Loss of advancement of the tibial tuberosity or tibial crest fractures did not occur in any case. One-stage revision surgery was successful in 5/7 cases (71%) with good long-term outcomes. Persistent infection resulted in removal of the replaced new cage in 2/7 cases (29%), of which one was associated with septic arthritis caused by multi-resistant bacteria. One-stage revision with immediate replacement of a new TTA cage successfully prevented loss of advancement of the tibial tuberosity and tibial crest fractures in this short case series. Further studies investigating possible improvements in the treatment protocol for refractory infection after TTA are warranted.
Keywords: tibial tuberosity advancement cage; one-stage revision; surgical site infection; dogs; implant removal